Second Language Learners’ Coping Strategy in Conversations with Native Speakers - Terui, Sachiko (Journal of International Students, 2012)
One of the many strategies that many international students employ to cope with their lack of English proficiency is to pretend to understand or not to understand the conversational content exchanged with native English speakers. Combining autoethnography and iterative interviews this research explores the pretending behavior profoundly from non-native speakers’ perspectives. During the iterative interviews, six students shared their personal experience specified in pretending behaviors. This study aims at informing the second language learning experience and promoting mutual understanding between native and non-native speakers in multi-lingual and multi-cultural societies. As a result, under the metatheme (Tesch, 1987) of pretending in conversation, pretending as a Communicative Strategy, eleven themes emerged.